Implementation of Spiral Modeling in the Design and Construction of the Paperless Office System for ITCC ITPLN Activity Documents - Mochamad Farid Rifai; Jatnika, Hendra; M. Yoga Distra Sudirman; Afifah Nurlita Octaviasari; Rizka Putri Aulia Rusdi; Fakhri Faros; M. Rafif Soniansyah (Politeknik Piksi Ganesha Indonesia, 2020)
The Information Technology Certification Center (ITCC) currently uses a manual system for creating financial accountability reports. This process is time-consuming and often leads to errors. Furthermore, because the necessary data is not centralized, data loss is a frequent problem, hindering the creation of accurate reports. To address these issues, the author developed